The ability of fruit and vegetable enzyme system to hydrolyse ester bonds - Agnieszka Mironowicz; Bogdan Jarosz; Antoni Siewiński (Acta Societatis Botanicorum Poloniae, 2014)
The pulp of potato tubers (Solanum tuberosum), topinambur (Helianthus tuberosus) and apples (Malus silvestris) can hydrolyse totally, or almost totally, ester bonds in phenyl, α- and β-naphthyl, benzyl and cinnamyl acetates. In methyl 4-acetoxy-3-metoxybenzoate and methyl 2,5-diacetoxybenzoate as well as testosterone propionate and 16,17-acetonide of 21-acetoxy-6-fluoro-16α,17β,21-trihydroxy-4-pregnen-3,20-dione, the hydrolysis is selective towards the substrate and the bioreagent. In contrast, ethyl benzoate and cinnamate are resistant to hydrolysis.